Efficiency of Marketing Systems of Cassava in Southeast, Nigeria - E. U. Eze; E. E. Osuji; C. O. Enyia; R. N. Nwose; G. U. Ugochukwu; A. C. Tim-Ashama; A. H. Odor; V. C. Nwogu; J. E. Orji; J. C. Nwaizuzu-Daniel (Emerging Issues in Agricultural Sciences Vol. 6, 2023)
The aim of the study is to examine the efficiency of the marketing systems of cassava in Southeast, Nigeria. The study objectives are to view global cassava production, access cassava production and marketing in Nigeria, and examine the marketing systems and its efficiency in Nigeria. Nigeria is the top producer of cassava, accounting for 20% of the global total of 303 million tonnes of cassava production in 2020. Democratic Republic of the Congo and Thailand were other important cassava growers in the world. Worldwide cassava production reached over 291 million tons in 2017, with Africa producing more than 60% of that total. State-level cassava production in Nigeria is dominated by the South-South States of Cross River, Akwa Ibom, Rivers, and Delta. About 70% of the total cassava production in Nigeria is produced in Ogun, Ondo, and Oyo in the South-West and Enugu and Imo in the South-East. However, prices for cassava in Nigerian markets differ from State to State and for the different by-products of cassava, including cassava starch, cassava flour, cassava chips, garri (eba), akpu (fufu), and abacha (bobozi/flakes). Cassava flour costs between 250,000 and 350,000 naira per ton, cassava starch costs between 300,000 and 450,000 naira per ton, and cassava chips cost on average 60,000 naira per ton. The study highlights the numerous stakeholders in cassava marketing, including producers, distributors, retailers, consumers, and processors. Efficiency in cassava marketing systems fosters effective price structures and encourages cassava value chain processes.